A short history of the Gaza Strip - Irfan, Anne (W.W. Norton & Company, 2025)
"Since October 2023, Israel has carried out one of the most brutal military onslaughts in modern history on the Gaza Strip, in response to the Hamas-led attacks of October 7. But Gaza had long been in crisis even prior to the current violence, now widely recognized as genocidal. For seventy-seven years, the Palestinian people have endured displacement, occupation, collective punishment, and ethnic cleansing - with those in Gaza often bearing the brunt of it. Historian Anne Irfan tells the story of the Gaza Strip through six pivotal moments in its modern history, beginning with Israel's expulsion of the Palestinian people upon its establishment in 1948, when Gaza absorbed more Palestinian refugees per head than anywhere else - a demographic shift that became central to its identity. As Irfan takes us through Israel's occupations of Gaza, the Palestinian national struggle and formation of the PLO, the first intifada, the creation of the Palestinian Authority, and the rise of Hamas, she tackles widespread historical ignorance and untangles contradicting narratives. Drawing on a decade of research, Irfan weaves in the voices of everyday Palestinians, from farmers who became refugees in Gaza to poets and activists who grew up in the Strip. Featuring a foreword from Gazan writer and analyst Muhammad Shehada, A Short History of the Gaza Strip is an indispensable read for anyone seeking to understand Palestine and its impact on the world." --